The Contribution of Customer Capital in Enhancing the Competitive Advantage: An Analytical Study of the Opinions of Employees in Internet Company’s in the Iraqi Governorate of Nineveh - Yehya , Alaa; Fathi, Ahmad (The Arab Journal of Administration, 2020)
The research aims, at showing the contribution of the customer capital which is considered as one of the main parts of intelligence capital, in achieving competitive advantage of the organization, It tackles the problem of little interest in the customer capital for the companies of internets, It depends on an analytical descriptive approach in testing hypotheses, and it arrives at a group of empirical concussions: The most important of these are: The results of the research revealed the interest of the companies in the capital to the customers and the most important regarding the needs and desires of future customers, and their satisfaction and loyalty to companies and it introduces suggestions for the tested organizations: The most important of which is to give the surveyed companies great attention to enhance the satisfaction of their customers and gain their loyalty by providing services of the right quality and in line with the needs and desires of the renewable customers to be guided by it in its attempt to a quire the competitive advantage in the market.